2007
DOI: 10.1007/s11664-007-0293-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UBM Thickness on the Mean Time to Failure of Flip-Chip Solder Joints under Electromigration

Abstract: Flip-chip solder joints with Cu/Ni/Al underbump metallurgy (UBM) on the chip and an Au/Ni surface finish on the substrate were studied under current stressing at an ambient temperature of 150°C. Three different Ni thicknesses in the Cu/Ni/Al UBM (0.3, 0.5, and 0.8 lm) were used in order to investigate the effect of the Ni thickness on reliability. The solder used was eutectic Pb-Sn, and the applied current density was 5 · 10 3 A/cm 2 . The results show that the combined effect of current crowding and the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The difference became more significant at a higher stressing due to serious heat generation, which in turn caused a higher resistance to electromigration. [24] Current biasing (mA) Figure 4 illustrates the lifetime difference (∆T) of Cu vs Ni UBMs. It is clearly demonstrate ∆T reduces in exponential decay function with current biasing.…”
Section: B Finite Element Modelingmentioning
confidence: 99%
“…The difference became more significant at a higher stressing due to serious heat generation, which in turn caused a higher resistance to electromigration. [24] Current biasing (mA) Figure 4 illustrates the lifetime difference (∆T) of Cu vs Ni UBMs. It is clearly demonstrate ∆T reduces in exponential decay function with current biasing.…”
Section: B Finite Element Modelingmentioning
confidence: 99%
“…Although the voids exist at the intermetallic layer, the electrical signal may still be able to transit through the voids and passes the functional test. Adding Ni layer is the most common solution to extend the lifetime by blocking the Cu/Sn IMC diffusion, as it is more resistant to dissolution into solder joints (Lin et al, 2008); yet, higher resistance will be because of the natural characteristic of Ni layer, and even some of the magnetic sensitive devices may have concern for adding these material; hence, the lifetime and void formation rate is extremely important for the device when to do the design from the initial stage.…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing simulation results, Liang et al found that joints with a thicker Cu UBM exhibited a lower maximum current density and hot spot temperature; the current crowding and local Joule heating effect vanished when the Cu UBM thickness was over than 50 µm (Liang et al 2006a). Moreover, Lin et al also reported that the joints with a thicker Ni UBM tend to have a longer electromigration lifetime (Lin et al 2008). The combination of current crowding and local Joule heating near the entrance point induced asymmetric of consumption Ni UBM.…”
Section: Introductionmentioning
confidence: 99%